2019
DOI: 10.3389/fpsyg.2019.01758
|View full text |Cite
|
Sign up to set email alerts
|

Inferiority or Even Superiority of Virtual Reality Exposure Therapy in Phobias?—A Systematic Review and Quantitative Meta-Analysis on Randomized Controlled Trials Specifically Comparing the Efficacy of Virtual Reality Exposure to Gold Standard in vivo Exposure in Agoraphobia, Specific Phobia, and Social Phobia

Abstract: Background: Convincing evidence on Virtual Reality (VR) exposure for phobic anxiety disorders has been reported, however, the benchmark and golden standard for phobia treatment is in vivo exposure. For direct treatment comparisons, the control of confounding variables is essential. Therefore, the comparison of VR and in vivo exposure in studies applying an equivalent amount of exposure in both treatments is necessary.Methods: We conducted a systematic search of reports published until June 2019. Inclusion crit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(160 citation statements)
references
References 105 publications
3
131
1
10
Order By: Relevance
“…More importantly, the complete control of the user's visual and auditory input makes it possible to create therapeutic experiences not available in the real world, for example being able to customize stimuli material to the user's idiosyncratic fears, or precisely manipulate the environment to target idiosyncratic catastrophic beliefs. Dozens of high-quality trials since the early 2000's support the efficacy of VR exposure therapy (VRET) for anxiety disorders (Carl et al, 2019;Fodor et al, 2018;Opriş et al, 2012), showing effect sizes similar to in-vivo exposure therapy (Wechsler et al, 2019) and that treatment effects generalize also to reduced fear of realworld equivalent phobic stimuli (Morina et al, 2015). Low rates of deterioration have also been found (Fernández-Álvarez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the complete control of the user's visual and auditory input makes it possible to create therapeutic experiences not available in the real world, for example being able to customize stimuli material to the user's idiosyncratic fears, or precisely manipulate the environment to target idiosyncratic catastrophic beliefs. Dozens of high-quality trials since the early 2000's support the efficacy of VR exposure therapy (VRET) for anxiety disorders (Carl et al, 2019;Fodor et al, 2018;Opriş et al, 2012), showing effect sizes similar to in-vivo exposure therapy (Wechsler et al, 2019) and that treatment effects generalize also to reduced fear of realworld equivalent phobic stimuli (Morina et al, 2015). Low rates of deterioration have also been found (Fernández-Álvarez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions on the usefulness of VRET, at least as a supplementary measure, were reached by other authors, also in the area of treating fear of driving and trauma after traffic accidents [ 79 , 80 , 81 , 82 ]. In some phobias, the effectiveness of in vivo exposure therapy seems similar to the effectiveness of VRET [ 83 , 84 ]. Therefore, it would be useful to test in the future whether physical motion simulations such as the one applied in our study—closer to an in vivo exposure than to VR—is as useful in reducing driving anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…"), and then proceed to examining effectiveness ("Does the intervention work under real-world conditions?"). In the case of VR exposure therapy for anxiety disorders, more than a dozen efficacy trials conducted over 20 years have convincingly shown that this intervention is efficacious (Carl et al 2019;Fodor et al 2018;Wechsler et al 2019) and associated with low rates of deterioration (Fernández-Álvarez et al 2019). To the author's knowledge, only a single effectiveness trial of VR exposure therapy has been published to date: although it demonstrated feasibility and replicated the effect size from the preceding efficacy trial, the sample size was relatively small and for ethical and practical reasons, a single-case design was chosen instead of comparison with treatment-as-usual (Lindner et al 2020a).…”
Section: Beyond Efficacy: Demonstrating Effectivenessmentioning
confidence: 99%
“…This narrative review will introduce readers to VR technology and how it can be put to clinical use, and discuss the past, present, and future of VR-CBT for mental disorders. The aim is not to provide a systematic review (Freeman et al 2017) or a meta-analysis of the field (Botella et al 2017;Carl et al 2018;Wechsler et al 2019) but rather to give a historical overview and context, showing how developments in technology have fueled clinical progress. Perspectives on the future of the field will also be provided.…”
Section: Introductionmentioning
confidence: 99%